Kidney involvement in monoclonal gammopathies: multidisciplinary approach in oncohematology and nephrology - A. V. Smirnov; V. A. Dobronravov; M. S. Khrabrova; B. V. Afanasyev (Онкогематология)
The pathogenetic relationship of kidney damage and an aberrant clone of the B-cell line producing nephrotoxic monoclonal immunoglobulin underlies the concept of “monoclonal gammopathy of renal significance” (MGRS). Herein the aberrant clone does not reach the criteria necessary for initiating antitumor therapy according to oncohematological indications. MGRS is a new nosology in modern nephrology and oncohematology. Monoclonal protein’s pathological effects on kidney parenchyma result in irreversible decline of kidney function till the end stage renal disease that in line with the position of International Consensus of hematologists and nephrologists determinates critical necessity for clone specific treatment in patients with MGRS despite the absence of hematological indications for treatment initiation. Main challenge of MGRS in Russian Federation is an inaccessibility of an in-time diagnostic and appropriate treatment for the great majority of patients due to the following reasons: i) limited knowledge about the MGRS among hematologists and nephrologists; ii) lack of necessary diagnostic resources in most health-care facilities; iii) lack of approved clinical recommendations and medical economic standards for treatment of this pathological entity. In order to overcome these limitations, leading oncohematologists and nephrologists of the Russian Federation on behalf of professional communities at the end of 2019 published a conciliation document: “Monoclonal gammopathy of renal significance: Consensus of hematologists and nephrologists of Russia on the establishment of nosology, diagnostic approach and rationale for clone specific treatment”. Consensus document comprises the opinion of experts – leading nephrologists and hematologists of Russian Federation – on the problem of MGRS including the incoherence in nosology classification, diagnostics approach and rationale for clone specific treatment. Consensus document is based on conclusions and agreements reached during the conference of leading nephrologists and hematologists of Russia which was held in the framework of symposia “Plasma cell dyscrasias and lymphoproliferative diseases: modern approaches to therapy”, 15–16 of March 2019, Pavlov First Saint Petersburg State Medical University, Saint Petersburg, Russia. Consensus is intended to define the principal practical steps to resolve the problem of MGRS in Russian Federation that are summarized as final clauses which we present here.